Enhanced bending-tuned magnetic properties in epitaxial cobalt ferrite nanopillar arrays on flexible substrates. Issue 2 (18th January 2018) - Shen, Lvkang; Liu, Ming; Ma, Chunrui; Lu, Lu; Fu, Huarui; You, Caiyin; Lu, Xiaoli; Jia, Chun-Lin
Abstract : Epitaxial (111) CoFe2 O4 nanopillar arrays were successfully grown on flexible fluorophlogopite substrates with strong bending-related magnetic properties. Abstract : Herein, large-scale epitaxial (111) CoFe2 O4 nanopillar arrays with an average nanopillar diameter of ∼40–60 nm and thicknesses of 26–700 nm have been obtained on flexible fluorophlogopite substrates by chemically etching the vertically aligned self-assembled CoFe2 O4 :MgO nanocomposite thin films. The chemical etching process has not affected the crystalline quality of the CoFe2 O4 phase, but results in volume shrinkage through the removal of the surrounding MgO phase. Compared with the planar CoFe2 O4 films, the nanopillar arrays show sharply declined coercivity and enhanced saturation magnetization. Even the thinnest nanoisland-shaped arrays (∼26 nm) retain a relatively high saturation magnetization (∼90 emu cc −1 ), nonzero coercivity (∼250 Oe), and remanence (∼30 emu cc −1 ), which are promising for the requirements of weak ferromagnetism in flexible devices. With an increase in the bending radius, a strong and monotonous increase in saturation/remanent magnetization has been found in the nanopillar arrays. This reveals that the bending-induced shape anisotropy as well as the intrinsic magnetocrystalline anisotropy mainly dominate the tunable magnetic properties in the CoFe2 O4 nanopillar arrays. With strong bending, the increment of remanent magnetization in the nanopillar arrays can be as high as 98%, exhibiting the huge potential of these nanopillar arrays in future applications such as in bending sensors and related devices.